How to Promote E-Commerce Exports to China: An Empirical Analysis - Min Jung Kim (KDI Journal of Economic Policy, 2017)
This paper focuses on the recent extraordinary growth of Chinese cross-border online shopping and draws implications for firm strategies and government policies in Korea to utilize the phenomenon as an opportunity to expand into a broader market via e-commerce exports. I conduct a survey of Chinese cross-border online consumers to identify constraining and determining factors during the stages of their purchase decisions of Korean products. Given the fact that Chinese cross-border online shopping is at the incipient stage and consumers have expressed a strong intent to repurchase, future strategies should focus on attracting new consumers. Accordingly, Korean firms should build a powerful brand image, improve product quality and post-purchase services, and take full advantage of the popularity of the Korean Wave. Meanwhile, the government must step up policy efforts by, for instance, improving e-commerce export statistics, simplifying logistics and clearance procedures, and building trust in Chinese consumers.
Keywords: L1; L81; M3; 330; Ecommerce export; Crossborder online shopping; Corporate strategy; Purchase decision making